Basic research in computer science and software engineering at SKLCS - Zhang, Jian; Zhang, Wenhui; Zhan, Naijun; Shen, Yidong; Chen, Haiming; Zhang, Yunquan; Wang, Yongji; Wu, Enhua; Wang, Hongan; Zhu, Xueyang (Frontiers of Computer Science, 2008)
The State Key Laboratory of Computer Science (SKLCS) is committed to basic research in computer science and software engineering. The research topics of the laboratory include: concurrency theory, theory and algorithms for real-time systems, formal specifications based on context-free grammars, semantics of programming languages, model checking, automated reasoning, logic programming, software testing, software process improvement, middleware technology, parallel algorithms and parallel software, computer graphics and human-computer interaction. This paper describes these topics in some detail and summarizes some results obtained in recent years.